Will Millennials save the world? The effect of age and generational differences on environmental concern. (15th July 2019) - Gray, Sara Goto; Raimi, Kaitlin T.; Wilson, Robyn; Árvai, Joseph
Abstract: Are younger people, defined by age, or younger generations, defined by cohort-level measures, more concerned about declines in environmental health when compared to their older counterparts within the United States? Related, are these same people more willing to support policy actions aimed at preventing future losses when compared to older adults? In spite of reporting by the U.S. popular press about the heightened environmental consciousness of Millennials, prior research offers conflicting answers. Scholarship focusing on age effects suggests that the answer to both questions is yes due to the dampening of environmental concern and action in older adults. More recent applied research on climate related risks and risk management options, by contrast, suggest that the answer to both questions is no, and that there is no difference in climate concern and risk mitigation between younger and older adults. In an attempt to disentangle these contradictory viewpoints, we undertook a study in which respondents in the United States characterized by age and generational cohort were presented with small and large hypothetical losses due to climate change. These same participants were then asked to indicate their support for future policy actions aimed at stemming these environmental losses. Overall, our data does not indicate that younger generations experience potential losses as more acute than older generations; neither age nor generational cohort correlated with the perceived severity of environmental losses nor support for future actions to prevent them. More robust predictors of both dependent variables were environmental value orientations (biospherism) and self-reported political orientation. Highlights: No patterns in response to environmental loss due to age or generation. Biospherism value positively predicts perceived severity of environmental loss. Increased biospherism results in commitment to take future environmental action. Politically conservative participants perceived low severity of environmental loss. Conservative political orientation led to decrease in future environmental action.